Polybacterial shift in benthic river biofilms attributed to organic pollution – prospect of a new biosentinel? - Exton, Benjamin; Hassard, Francis; Medina, Angel; Grabowski, Robert C. (IWA Publishing, 2023)
Organic pollution continues to contaminate river water and degrade aquatic ecosystems worldwide. In heavily modified river systems with high organic loading, sewage fungus, a heterotrophic biofilm, can form on the riverbed. The aim of this study was to determine how the polybacterial community of riverbed biofilms changes prior to and during a sewage fungus outbreak to inform the development of novel biomonitoring approaches. Riverbed biofilm samples were collected from a site that experienced sewage fungus outbreaks previously and an upstream control, following a BACI design. The polybacterial community was characterized using targeted amplicon sequencing (16s rRNA). The results indicate that the community became dominated by two genera prior to and during the sewage fungus outbreak, Rhodoferax and Sphaerotilus, which accounted for 32.8 and 14.2% of the relative abundance. When aggregated at a higher taxonomic level, the genetic data show that the community was comprised largely of bacteria from a single family, Comamonadaceae, totalling 64.1% of the relative abundance. Statistically significant differences in the polybacterial community over time and between impact and control sites provide initial evidence that genetic-based fingerprinting could be a promising biosentinel approach to identify organic pollution inputs and monitor their ecological impact.
Keywords: 16s rRNA amplicon analysis; bioindicator; Rhodoferax; sewage fungus; Sphaerotilus; water quality